The Effect of Coronary Artery Disease on the Prognosis of Hypertrophic Cardiomyopathy: A Multi-Center Cohort Study - Guoqing Hou; Qian Liao; Huihui Ma; Yan Shu; Shengzhi Zeng; Yongmei Zhou; Liangjun Luo; Gang Zhao; Tao He; Mingjiang Liu; Jianhong Tao; Wei Hua; et al. (Reviews in Cardiovascular Medicine)
Background: There is a shortage of patients with hypertrophic cardiomyopathy (HCM) with concurrent coronary artery disease (CAD), and the influence of CAD on the prognosis of patients with HCM is uncertain. This real-world cohort study was conducted to evaluate the prognosis of patients with patients with CAD. Methods: This cohort study of patients with HCM was conducted from May 2003 to September 2021. The total number of patients enrolled was 2167, and the mean follow-up period was 6.4 years (interquartile range 2.8–9.5 years). Sudden cardiac death (SCD), cardiovascular death, and all-cause mortality were assessed as outcomes. Using logistic regression, nine indicators were selected for 1:1 propensity score matching (PSM). Additionally, Kaplan–Meier survival curves and Cox proportional hazards regression analyses were used to assess the impact of CAD on the prognosis of patients with HCM. Results: During an average of 6.4 years of follow-up, of the 2167 patients enrolled, 446 (20.6%) died. The patients were classified into two groups: CAD (n = 480) and non-CAD (n = 1,687). After imputation of missing values using the mean and 1:1 propensity score matching, there was no difference in SCD (log-rank χ2 = 0.4, p = 0.540), cardiovascular death (log-rank χ2 = 0.1, p = 0.995) and all-cause mortality (log-rank χ2 = 0.1, p = 0.776) between the CAD and non-CAD groups. After imputation of missing values using the median and 1:1 propensity score matching, patients with and without CAD were not significantly different in terms of SCD (log-rank χ2 = 0.1, p = 0.948), cardiovascular death (log-rank χ2 = 0.1, p = 0.811), and all-cause mortality (log-rank χ2 = 0.5, p = 0.499). In the Cox analysis, CAD was not a significant independent predictor of SCD, cardiovascular death, or all-cause mortality in patients with HCM. Conclusions: In this study, it was observed that there was no statistically significant disparity in mortality rates between patients diagnosed with HCM who concurrently had CAD and those who did not exhibit CAD. This finding underscores the notion that the presence of CAD did not exert a notable influence on the incidence of SCD, cardiovascular death, or all-cause mortality, thereby emphasizing the complexity and multifaceted nature of mortality risk factors in HCM patients.